APLIKASI KOMPOS JERAMI PADI DI MEDIA GAMBUT UNTUK MENINGKATKAN PERTUMBUHAN BIBIT KOPI LIBERIKA - Sopiana, Sopiana; fitry ramanda, Rika; Kurniawan, Tardi; Rosmalinda, Rosmalinda; Mahruf, Hafif (Politeknik Negeri Ketapang, 2024)
The use of peat media for coffee cultivation needs to be considered because peat soil has problems such as low soil pH and low nutrient content. Using rice straw compost is an alternative for increasing nutrient levels in peat soil. Rice straw compost contains 0.5-0.8% nitrogen, 0.07-0.12% phosphorus, 1.2-1.7% potassium and 7% silicon. This research aims to determine the best dose of rice straw compost so that it can increase the growth of Liberica coffee seedlings in peat media. The research used a completely randomized design (CRD) consisting of 5 treatments and 5 replications. The treatments were K₀: without rice straw compost, K₁: 150 g/plant K₂: 175 g/plant, K₃: 200 g/plant, K₄: 225 g/plant. The parameters observed were plant height, stem diameter, number of leaves, leaf length, root length and plant dry weight. The research data were analyzed statistically using Analysis of Variance (ANOVA). Data that had a real effect were further tested using the Duncan Multiple Range Test (DMRT) at the 5% level. The application of rice straw compost in peat media had a significant effect on the growth of seedling height, stem diameter, number of leaves, root length and dry weight of Liberica coffee seedlings. Rice straw compost at a dose of 225 g/plant applied in peat media is the best dose because it increases the vegetative growth of Liberica coffee seedlings.